Plasmid-Mediated Ampicillin, Quinolone, and Heavy Metal Co-Resistance among ESBL-Producing Isolates from the Yamuna River, New Delhi, India - Mohammad Tahir Siddiqui; Aftab Hossain Mondal; Firdoos Ahmad Gogry; Fohad Mabood Husain; Ali Alsalme; Qazi Mohd. Rizwanul Haq (MDPI AG, 2020)
Antibiotic resistance is one of the major current global health crises. Because of increasing contamination with antimicrobials, pesticides, and heavy metals, the aquatic environment has become a hotspot for emergence, maintenance, and dissemination of antibiotic and heavy metal resistance genes among bacteria. The aim of the present study was to determine the co-resistance to quinolones, ampicillin, and heavy metals among the bacterial isolates harboring extended-spectrum β-lactamases (ESBLs) genes. Among 73 bacterial strains isolated from a highly polluted stretch of the Yamuna River in Delhi, those carrying blaCTX-M, blaTEM, or blaSHV genes were analyzed to detect the genetic determinants of resistance to quinolones, ampicillin, mercury, and arsenic. The plasmid-mediated quinolone resistance (PMQR) gene qnrS was found in 22 isolates; however, the qnrA, B, C, and qnrD genes could not be detected in any of the bacteria. Two variants of CMY, blaCMY-2 and blaCMY-42, were identified among eight and seven strains, respectively. Furthermore, merB, merP, merT, and arsC genes were detected in 40, 40, 44, and 24 bacterial strains, respectively. Co-transfer of different resistance genes was also investigated in a transconjugation experiment. Successful transconjugants had antibiotic and heavy metal resistance genes with similar tolerance toward antibiotics and heavy metals as did their donors. This study indicates that the aquatic environment is a major reservoir of bacteria harboring resistance genes to antibiotics and heavy metals and emphasizes the need to study the genetic basis of resistant microorganisms and their public health implications.